2023
DOI: 10.1101/2023.01.10.523481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial transcriptomics analysis of neoadjuvant cabozantinib and nivolumab in advanced hepatocellular carcinoma identifies independent mechanisms of resistance and recurrence

Abstract: Novel immunotherapy combination therapies have improved outcomes for patients with hepatocellular carcinoma (HCC), but responses are limited to a subset of patients and recurrence can also occur. Little is known about the inter- and intra-tumor heterogeneity in cellular signaling networks within the HCC tumor microenvironment (TME) that underlie responses to modern systemic therapy. We applied spatial transcriptomics (ST) profiling to characterize the tumor microenvironment in HCC resection specimens from a cl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…67 The critical roles of B cells in mediating immunotherapy response have been highlighted by spatial transcriptome analysis of resection specimens from 15 HCC patients involved in a neoadjuvant trial, five of which achieved pathological responses. 75 As expected, a lack of clinical response was tightly correlated with an absence of immune infiltration into the tumor. In the responders, activation of PAX5 signaling in the immune regions adjacent to tumor clusters was detected.…”
Section: B Cellssupporting
confidence: 63%
“…67 The critical roles of B cells in mediating immunotherapy response have been highlighted by spatial transcriptome analysis of resection specimens from 15 HCC patients involved in a neoadjuvant trial, five of which achieved pathological responses. 75 As expected, a lack of clinical response was tightly correlated with an absence of immune infiltration into the tumor. In the responders, activation of PAX5 signaling in the immune regions adjacent to tumor clusters was detected.…”
Section: B Cellssupporting
confidence: 63%
“…Remarkably, our ndings unveiled that the Neo-surgery cohort exhibited prolonged OS and PFS compared to their counterparts undergoing immediate surgical intervention. Preclinical investigations and correlative analyses lend credence to the hypothesis that neoadjuvant therapy leads a localized tumor response and mitigates recurrence by modulating the tumor microenvironment, a phenomenon observed across various therapeutic modalities, including immune-based interventions 32,33 . Numerous synergistic mechanisms contributing to the effectiveness of neoadjuvant therapy in HCC have been elucidated.…”
Section: Discussionmentioning
confidence: 92%
“…However, due to a lack of spatial resolution, outputs from QSP models cannot be fully compared with quantitatively analyzed histopathological samples from tumors, including measures of intratumoral heterogeneity 19 . Our spatial transcriptomics analysis has demonstrated that spatial heterogeneity can result in distinct tumor immune microenvironments, leading to resistance and recurrence to immunotherapy in liver cancer 20 . To fully utilize the wealth of information contained in the spatial data in the TME, we coupled an agent-based model (ABM) with our whole-patient QSP platform to formulate a spatial QSP model (spQSP).…”
Section: General Information and Clinical Trial Results For Hccmentioning
confidence: 99%
“…Together, using this new computational model a virtual clinical trial is conducted that simulates both patient outcomes and spatially resolved molecular states of tumors. We benchmark our computational model by comparing the simulated state of the TME to high-dimensional spatial proteomics and transcriptomics data from post-treatment tumor resections in the original clinical trial 3,20,24 . Whereas the biospecimens for the neoadjuvant clinical trial were only obtained at the time of surgery, the spQSP model fully simulated the spatial molecular states of the tumors over time.…”
Section: General Information and Clinical Trial Results For Hccmentioning
confidence: 99%